2021
DOI: 10.2147/dmso.s309725
|View full text |Cite
|
Sign up to set email alerts
|

Early Prediction Model of Gestational Hypertension by Multi-Biomarkers Before 20 Weeks Gestation

Abstract: Background Gestational hypertension (GH), a hypertensive disorder of pregnancy (HDP), is a leading cause of maternal and fetal mortality due to the lack of clarity on its exact etiology and clinically feasible prediction models. This study was performed to discover novel biomarkers before 20 weeks gestation and thereby construct an early GH prediction model. Methods This study was designed based on differentially expressed protein screening followed by clinical validati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
(61 reference statements)
0
4
2
Order By: Relevance
“…In a large‐scale study, thrombophilia was reported to be significantly associated with severe PE, 32 but plasma ATIII levels were did not differ significantly between the group of patients with PE and the control group 33 . Zhou et al emphasized that SERPINC1 levels were significantly higher in women who developed gestational hypertension before 20 weeks of gestation than in those women with uncomplicated pregnancies 34 . On the contrary, in our study, the serum levels of SERPINC1 in the group of patients with EO‐PE were significantly lower than the levels measured in the LO‐PE group and the control group.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…In a large‐scale study, thrombophilia was reported to be significantly associated with severe PE, 32 but plasma ATIII levels were did not differ significantly between the group of patients with PE and the control group 33 . Zhou et al emphasized that SERPINC1 levels were significantly higher in women who developed gestational hypertension before 20 weeks of gestation than in those women with uncomplicated pregnancies 34 . On the contrary, in our study, the serum levels of SERPINC1 in the group of patients with EO‐PE were significantly lower than the levels measured in the LO‐PE group and the control group.…”
Section: Discussioncontrasting
confidence: 92%
“…33 Zhou et al emphasized that SER-PINC1 levels were significantly higher in women who developed gestational hypertension before 20 weeks of gestation than in those women with uncomplicated pregnancies. 34 On the contrary, in our study, the serum levels of SERPINC1 in the group of patients with EO-PE were significantly lower than the levels measured in the LO-PE group and the control group. SERPINC1 levels of the patients with LO-PE were significantly lower than the levels measured in the control group.…”
Section: Discussioncontrasting
confidence: 85%
“…To gain insights into the identified proteins’ dynamics during hypertensive vs normotensive pregnancies, we performed a systematic review of studies reporting observational associations of the prioritized proteins with HDPs. Forty-three studies met our inclusion criteria (eFigure 3 in Supplement 1), encompassing 9749 pregnant individuals with protein measurements who enrolled from 1998 to 2020 in their respective studies. Of those, 3122 individuals (32.0%) experienced an HDP, including 939 (9.6%) with gestational hypertension, 2167 (22.2%) with preeclampsia, and 16 (0.2%) without information on HDP subtype.…”
Section: Resultsmentioning
confidence: 99%
“…Patients with a history of hypertension, kidney disease, or other conditions causing elevated blood pressure prior to the 20 th week of gestation were excluded. In addition, cases of primary lipid metabolism abnormalities, stillbirth, miscarriage, multiple pregnancies, fetal malformation, thyroid disease, gestational diabetes, and liver and kidney diseases were excluded [ 16 ].…”
Section: Methodsmentioning
confidence: 99%